How 'atypical' is the neuroimaging signature of Alzheimer's atypical variants? MRI and PET imaging of posterior cortical atrophy and logopenic variant of primary progressive aphasia: Featured research and focused topic sessions: An update on the pathological, imaging and clinical features underlying heterogeneity across individuals with Alzheimer's disease. (7th December 2020) - Joie, Renaud La; Damasceno, Pablo F.; Visani, Adrienne; Iaccarino, Leonardo; Strom, Amelia; Edwards, Lauren; Gorno‐Tempini, Marilu; Jagust, William J.; Miller, Bruce L.; Raj, Ashish; Rabinovici, Gil D.
Abstract: Background: Alzheimer's disease clinical expression is highly heterogeneous: cognitive and anatomical variations exist on a multi‐axis spectrum with well‐described variants like posterior cortical atrophy (PCA) or logopenic variant of primary progressive aphasia (lvPPA) representing extreme phenotypes of so‐called "atypical" AD. Here, we provide an overview of our investigations of PCA and lvPPA using structural MRI and amyloid/tau‐PET imaging, emphasizing both the differences and the similarities between these phenotypes and more typical presentations of AD. Method: We investigated 97 amyloid‐positive patients with a clinical diagnosis of AD (MCI or dementia stage), including 18 patients with PCA and 19 with lvPPA; the remaining patients are referred to as typical (tAD; Table 1). Patients received 3‐tesla MRI and PET with [11C]PIB and [18F]Flortaucipir. Standardized Uptake Value Ratio (SUVR) images were created using specific reference regions. Mean SUVR or cortical thickness values were extracted from 72 FreeSurfer regions, and cortical asymmetry indices were calculated. Result: Atypical variants tended to be younger and less likely to carry APOE4 than tAD (Table1). Global amyloid burden did not vary across phenotypes or with any clinical measure (Figure 1A). The cortical distribution of PIB was widespread and only showed minor differences between variants (Figure 2A). In contrast, global Flortaucipir‐SUVR was higher in atypical groups compared to tAD, and was lower in older patients across phenotypes (Figure 1A). Flortaucipir was consistently elevated in temporo‐parietal regions but also showed strong between‐variant regional differences (Figure 2B) that mirrored differences in cortical volume (Figure 3B). Flortaucipir and MRI asymmetries were strongly inter‐related and very common across all AD phenotypes rather than specific to atypical variants (Figure 3). However, asymmetry was systematic in lvPPA (84‐95% left‐predominant, 5% right‐predominant) and PCA (33% left‐predominant, 66% right‐predominant) Conclusion: Atypical phenotypes share various features with tAD: i) widespread cortical amyloid deposition, ii) tau pathology in the temporo‐parietal areas, iii) higher tau burden associated with earlier disease onset, iv) a strong negative relationship between tau and local cortical volume. The main between‐phenotype differences were related to the distribution of tau and associated atrophy that were more left‐predominant and perisylvian in lvPPA, and more occipital and asymmetric in PCA.